The public, the news media and probation in England and Wales - Collins, Stewart (European journal of probation, 2025)
The main aim of this article is to present and analyse literature and research focused upon public perceptions of probation and portrayals of probation in print, on-line and broadcast news media in England and Wales. A brief account is provided of historical developments in probation in those countries over the past 50 years. Public perceptions of crime, community sentencing, the wider criminal justice system and, in particular probation, are critically explored. Analysis is presented of attempts to publicise probation work. The varied impact of news media upon the public in England and Wales about crime, community sentencing, the criminal justice system and probation is analysed. Past and present responses to news media by probation are also critically evaluated. Suggestions are made for further research, for improvements in communication between probation organisations, the public and news media, drawing upon existing research and examples from social work and other countries.